2011
DOI: 10.1017/s000305541000047x
|View full text |Cite
|
Sign up to set email alerts
|

How Large and Long-lasting Are the Persuasive Effects of Televised Campaign Ads? Results from a Randomized Field Experiment

Abstract: W e report the results of the first large-scale experiment involving paid political advertising. During the opening months of a 2006 gubernatorial campaign, approximately $2 million of television and radio advertising on behalf of the incumbent candidate was deployed experimentally. In each experimental media market, the launch date and volume of television advertising were randomly assigned. In order to gauge movement in public opinion, a tracking poll conducted brief telephone interviews with approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
237
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 458 publications
(278 citation statements)
references
References 44 publications
23
237
2
5
Order By: Relevance
“…1 A handful of recent studies, however, has found that persuasion effects can be quite shortlived, decaying in a few weeks or even a few days. Best known is the Texas advertising study, which found no persistence of persuasion effects in the week following exposure to the ads (Gerber, Gimpel, Green, and Shaw, 2011). But other recent studies show similar results.…”
mentioning
confidence: 91%
“…1 A handful of recent studies, however, has found that persuasion effects can be quite shortlived, decaying in a few weeks or even a few days. Best known is the Texas advertising study, which found no persistence of persuasion effects in the week following exposure to the ads (Gerber, Gimpel, Green, and Shaw, 2011). But other recent studies show similar results.…”
mentioning
confidence: 91%
“…Yet in comparison to the extensive literatures investigating the political influence of traditional media such as newspaper coverage (e.g., Mondak 1995;Ladd and Lenz 2009) and television broadcasts (e.g., Iyengar 1991;Gerber et al 2011a), the research literature on internet advertising remains sparse.…”
mentioning
confidence: 99%
“…Statistically significant decrements in psychological distress were evident in the neighborhood in which the ads appeared, public response in social media was animated, and a broad community impact was observed, generating further evidence of the hypothesized mechanisms that would drive change. In describing their research on the impact of television advertising on voter preferences, Gerber et al 54 contend, "It should come as no surprise that a study such as this one generates as many research questions as it answers. This experiment is among the first in any discipline to estimate the effects of a large-scale media campaign using random assignment" (p. 149).…”
Section: Resultsmentioning
confidence: 99%
“…For product advertising, attitudes towards the product and purchase intention decay rapidly; in politics, advertising has a half-life of 2-3 days to 1 week, with effects decaying more rapidly for the least politically aware. 54 Although high volume TV ads ($3 million per week) can exert a strong effect on voter preferences, shifting the target candidate's standing by six percentage points, these effects are smaller and statistically equivocal effects one week later, and vanquished thereafter. 54 Decay was apparent among RISE participants, as indicated by recall of ad content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation